Nursing Skills in Handling Earthquakes and the Implications for Nursing Education: A Narrative Review - Setiawan, Deris Riandi; Emaliyawati, Etika; Trisyani, Yanny; Nuraeni, Aan; Noya, Fricilia; Harlasgunawan, Alia Rahmi; Rahman, Luthfi; Sugiharto, Firman (Media Karya Kesehatan, 2025)
Many countries have high earthquake activities. As an integral part of the emergency response team, nurses play a critical role in disaster management. This review aimed to identify nurses' skills in dealing with earthquakes and their implications for the importance of nurse education in this area. This study used a narrative review. The literature was searched using three databases: CINAHL, PubMed, and Scopus, using the keywords "Nurses OR Nurse OR Personnel Nurses OR Registered Nurses AND Clinical Competence OR Competency, Clinical OR Clinical Skill AND Earthquakes." The analysis was carried out descriptively and qualitatively using a thematic analysis approach. The resultsshows that eight studies were analyzed in this review. Nursing competency in earthquake disasters includes skills and knowledge important for preparing, responding to, and recovering from pre- and post-disaster conditions. The results of this research classify nurses' skills into five categories: knowledge of disaster management, clinical skills and patient care, protective measures and safety leadership, communication and coordination, and psychological and social support. Conclusion: The review results highlight the importance of increasing nurses' skills through training and knowledge in disaster preparedness for nurses, emphasizing a deep understanding of emergency medical management and post-disaster recovery. The importance of adapting nursing education curricula and using effective teaching strategies to ensure that nurses have sufficient skills and knowledge to face complex disaster challenges. Keywords: Clinical competence, disaster management, nursing skills.